HUBUNGAN EKONOMI KELUARGA TERHADAP PERENCANAAN KARIR SISWA KELAS XI SMAN 15 PALEMBANG - Fitria, Indri Titis; Sucipto, Sigit Dwi (CV. Jendela Gagasan, 2024)
When a student is a teenager, making career plans is quite confusing and challenging, because before making a career decision there are many things that should be considered, because career planning is influenced by several factors, one of which is the family economy. This research uses a quantitative approach with a correlation method which aims to determine the relationship between family economics and career planning for SMA Negeri 15 Palembang students. Data collection was distributed using a Google form which was distributed to 74 respondents as research samples. The data analysis technique uses the Pearson product moment formula. The results of the correlation coefficient above obtained an r value of 0.231, then to find the r table based on a sample of 74 people with a significance level of 5%, we obtained 0.192 as the r table value. Based on these results it can be concluded that accept H1 or reject H0, or there is a relationship between family economic variables and career planning in the low category and in the same direction, meaning that if the family economic level is high, then the student's career planning is also high, conversely if the family economic level is low then career planning students are also low.